ANALISIS PERBANDINGAN KINERJA KEUANGAN PADA PD BPR BKK KEBUMEN DAN PT BPR DANA MITRA SEJAHTERA KEBUMEN - Erma Reiza Damayanti; Dyah Fitriani (Jurnal Fokus Manajemen Bisnis, 2015)
The research aims to comparehealth of BPR in terms of financial performance. The object  of  the research  is  PD  BPR  BKK  Kebumen  and  PT  BPR Dana  Mitra  Sejahtera  for  a period of 2012,2013 and 2014.  Banking  financial  performance used  on  this  research  is on financial aspects that be measured by the ratio of the suffciency minimum obligation (CAR), the ratio of the quality of assets productive (KAP), an allowance the formation of productive assets (PPAP), the ratio return on assets (ROA) that reflect the ability of a bank in generate profit, the  ratio  of  BOPO ( the  load operational  against operational  income)  that  reflects the burden of operational compared with earnings obtained, while for liquidity measured by CR and LDR. From this research obtained the results of that overall shows the  level of  financial performance  of  a  healthy.  The  ratio  CAR  in  PD  BPR  BKK  Kebumen  shows  the  average 15,21% larger from PT BPR Dana Mitra Sejahtera that shows the average CAR 12,70% and both banks included in category of healthy. The rati of the quality of assets productive (KAP) in PD BPR BKK  Kebumen  shows the average 5,68% larger than PT Dana Mitra Sejahtera which  shows  the  average  quality  of  assets productive  5,27%  and  both  banks  included  in category  of  healthy.  The  ratio  of  PPAP  inPD  BPR  BKK  Kebumenthat  shows  the  average 100% and PT BPR Dana Mitra Sejahtera which shows the average 95,68% and both banks included  in  category  of  healthy.  The  ratio  ROA  in  PD  BPR  BKK  Kebumen  shows  the average 3,64% larger than PT BPR Dana Mitra Sejahtera which shows the the average ROA 2,24% and both banks included in category of healthy.the ratio of BOPO in PD BPR BKK Kebumen  shows  the  average  72,13%  less  than  than  funds  PT  BPR  Dana  Mitra  Sejahtera which shows the average BOPO 75,68% and both banks included in category of healthy. The ratio of CR in PD BPR BKK Kebumen shows the average 25,82% larger from PT BPR Dana Mitra  Sejahtera  thatshows  the  average  CR  21,02%  and  both  bank  included  in  category  of healthy. The ratio LDR in PD BPR BKK Kebumen shows the average 98,90% and included in  category  of  less  healthy  and  this  is  different  from  PT  BPR  Dana  Mitra  Sejahtera  that Shows the average 78,33% in categories healthy. The ratio of non performing loan (NPL) in PD BPR BKK Kebumen shows the average 3,87% and dutifully included in the category of while from PT BPR Dana MitraSejahtera which shows the average NPL 5,25% greater than that  required  in  category  5%  so  dutifully  enough.  Of  a  whole  the  assessment  of  the  level second health BPR in PT BPR Dana Mitra Sejahtera it has value 99.90 % better than PD BPR BKK kebumen in that it has value 99.05 %.